2021
DOI: 10.1111/jgs.17477
|View full text |Cite
|
Sign up to set email alerts
|

Changes in activity levels, physical functioning, and fall risk during the COVID‐19 pandemic

Abstract: Background: Physical function worsens with older age, particularly for sedentary and socially isolated individuals, and this often leads to injuries. Through reductions in physical activity, the COVID-19 pandemic may have worsened physical function and led to higher fall-related risks. Methods: A nationally representative online survey of 2006 U.S. adults aged 50-80 was conducted in January 2021 to assess changes in health behaviors (worsened physical activity and less daily time spent on feet), social isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 42 publications
1
61
1
1
Order By: Relevance
“…In this analysis of data from the nationally representative Medicare Current Beneficiary Survey, our findings support prior research demonstrating increases in loneliness and feeling socially disconnected since the start of the COVID‐19 pandemic 1–5 . We expand upon previous findings by looking specifically at those aged 65 years and older using nationally representative data.…”
Section: Discussionsupporting
confidence: 82%
“…In this analysis of data from the nationally representative Medicare Current Beneficiary Survey, our findings support prior research demonstrating increases in loneliness and feeling socially disconnected since the start of the COVID‐19 pandemic 1–5 . We expand upon previous findings by looking specifically at those aged 65 years and older using nationally representative data.…”
Section: Discussionsupporting
confidence: 82%
“…What is not visible from our data is the longer-term consequences of a COVID-19–related decline in activity. In a survey conducted in January 2021, one third of American older adults reported reduced activity levels since the start of the pandemic ( Hoffman et al, 2021 ). Associated with the reduced activity was a two to threefold worsening of self-reported physical function as well as increased risk of falls and fear of falling ( Hoffman et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a survey conducted in January 2021, one third of American older adults reported reduced activity levels since the start of the pandemic ( Hoffman et al, 2021 ). Associated with the reduced activity was a two to threefold worsening of self-reported physical function as well as increased risk of falls and fear of falling ( Hoffman et al., 2021 ). These findings suggest a tipping point—perhaps not yet reached by the time of our study—at which a step count reduction leads to muscle loss, physical deconditioning, and falls.…”
Section: Discussionmentioning
confidence: 99%
“…We found that concern about the pandemic and reported changes in health routines were common and associated with substantially lower scores for perceived physical functioning and community mobility and social participation, consistent with patterns observed in older adults. [11][12][13] In this cross-sectional study, we cannot determine whether these observed associations reflect true causal associations. We also cannot know the direction of the associations, or whether these associations differ from those in the population without SLE.…”
Section: Discussionmentioning
confidence: 84%